2021
DOI: 10.1371/journal.pntd.0008984
|View full text |Cite
|
Sign up to set email alerts
|

Congenital abnormalities associated with Zika virus infection–Dengue as potential co-factor? A systematic review

Abstract: Zika virus (ZIKV) emerged in Brazil during 2013–2014 causing an epidemic of previously unknown congenital abnormalities. The frequency of severe congenital abnormalities after maternal ZIKV infection revealed an unexplained geographic variability, especially between the Northeast and the rest of Brazil. Several reasons for this variability have been discussed. Prior immunity against Dengue virus (DENV) affecting ZIKV seems to be the most likely explanation. Here we summarise the current evidence regarding this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…ADE, in which virus uptake and infection are increased via the interaction of cellular Fcγ receptors with an antibody-bound (but not neutralized) virus, has been most prominently demonstrated during sequential infection with heterologous serotypes of dengue virus [ 79 ]. ADE of ZIKV infection has also been demonstrated with anti-DENV antibodies in vitro and in mice [ 80 ], although not in NHPs or humans [ 81 , 82 , 83 , 84 , 85 ]. However, the ability of maternal antibodies to enhance ZIKV infection in culture demonstrated a positive correlation between enhancement titers and adverse pregnancy outcomes in humans and NHPs [ 86 ], suggesting that placental FcRn receptors may mediate increased uptake of the virus.…”
Section: Maternal and Fetal Immune Response To Zikv Infectionmentioning
confidence: 99%
“…ADE, in which virus uptake and infection are increased via the interaction of cellular Fcγ receptors with an antibody-bound (but not neutralized) virus, has been most prominently demonstrated during sequential infection with heterologous serotypes of dengue virus [ 79 ]. ADE of ZIKV infection has also been demonstrated with anti-DENV antibodies in vitro and in mice [ 80 ], although not in NHPs or humans [ 81 , 82 , 83 , 84 , 85 ]. However, the ability of maternal antibodies to enhance ZIKV infection in culture demonstrated a positive correlation between enhancement titers and adverse pregnancy outcomes in humans and NHPs [ 86 ], suggesting that placental FcRn receptors may mediate increased uptake of the virus.…”
Section: Maternal and Fetal Immune Response To Zikv Infectionmentioning
confidence: 99%
“…In non-pregnant macaque studies, the presence of DENV IgG does not increase ZIKV titers or disease [ 7 , 8 ]. Human pregnancy studies have begun teasing apart this question by examining pregnancies with prenatal ZIKV exposure and DENV immunity, and defining rates of miscarriage, abnormal infant physical exams, congenital Zika syndrome, and abnormal infant neuroimaging [ 9 ]. The role of maternal DENV immunity on prenatal ZIKV infection varies between the populations studied, with some studies identifying no change in the rates of miscarriage and microcephy [ 10 , 11 , 12 ], and others finding that maternal DENV immunity may reduce the risk of congenital Zika syndrome [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro and mouse studies reported that preexisting anti-DENV immunity associated with ZIKV pathogenesis via antibody-dependent enhancement (ADE) (Stettler et al, 2016;Bardina et al, 2017;Rathore et al, 2019); however, clinical and epidemiological evidence for ADE has not been provided yet. In contrast, human studies demonstrated that previous DENV immunity had no or cross-protection impact against ZIKV infection (Halai et al, 2017;Moreira-Soto et al, 2017;Castanha et al, 2019;Pedroso et al, 2019;Katzelnick et al, 2020;Michlmayr et al, 2020;Tonnerre et al, 2020;Petzold et al, 2021). In the Nicaraguan and Brazil pediatric cohorts, prior DENV infection and pre-existing anti-NS1 DENV antibodies were associated with reduced risk of ZIKV infection and disease (Gordon et al, 2019;Rodriguez-Barraquer et al, 2019).…”
Section: Non-mutation Based Potential Factors Responsible For the Recent Zikv Emergencementioning
confidence: 97%